Exposure to Motivational Messages Promotes Meritocratic Beliefs and an Individualistic Perception of Social Change - Vázquez, Alexandra (2023)
Some critics claim that the self-help industry legitimizes inequality by enhancing individualism and meritocratic beliefs. The present research aims to provide experimental support to these assumptions by exploring the effect of motivational messages on meritocratic beliefs and the perceived effectiveness of individual and collective action to promote social change toward equality and on collective action intentions. Across three experiments, 663 participants were exposed to motivational messages either by copying short quotes or watching a short video containing those same quotes. As compared with a control condition, exposure to motivational messages strengthened meritocratic beliefs and, in turn, increased the perceived effectiveness of individual action in promoting social change and undermined the perceived effectiveness of collective action and subsequently collective action intentions. These findings fuel the debate on the individualistic bias and meritocratic orientation of the self-help industry and highlight the need to analyze its impact on social and economic justice.